2022
DOI: 10.3390/ijms23105819
|View full text |Cite
|
Sign up to set email alerts
|

The Rice Malectin Regulates Plant Cell Death and Disease Resistance by Participating in Glycoprotein Quality Control

Abstract: In animals, malectin is well known to play an essential role in endoplasmic reticulum quality control (ERQC) by interacting with ribophorin I, one unit of the oligosaccharyltransferase (OST) complex. However, the functions of malectin in plants remain largely unknown. Here, we demonstrate the rice OsMLD1 is an ER- and Golgi-associated malectin protein and physically interacts with rice homolog of ribophorin I (OsRpn1), and its disruption leads to spontaneous lesion mimic lesions, enhanced disease resistance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 99 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…In rice, the MALECTIN LIKE-DOMAIN PROTEIN MLD1 located in the ER may play a similar role to its mammalian homologs in glycoprotein quality control, thereby regulating cell death and immunity [ 175 ]. However, most MAL-domain-containing proteins in plants are RLKs in the plasma membrane with their MAL regions in the extracellular space.…”
Section: Mal Domain Rlksmentioning
confidence: 99%
“…In rice, the MALECTIN LIKE-DOMAIN PROTEIN MLD1 located in the ER may play a similar role to its mammalian homologs in glycoprotein quality control, thereby regulating cell death and immunity [ 175 ]. However, most MAL-domain-containing proteins in plants are RLKs in the plasma membrane with their MAL regions in the extracellular space.…”
Section: Mal Domain Rlksmentioning
confidence: 99%
“…Meanwhile, LETUM1, a malectin-like RLK, regulates autoimmunity in Arabidopsis by interacting with SUMM2 and MEKK2 and forming a complex [ 32 ]. Malectin/malectin-like domain proteins play important roles in other physiological processes, such as pollen and seed development, growth, disease resistance, and survival [ 33 , 34 , 35 , 36 , 37 ]. Moreover, we identified that R. solani significantly induced MDPK [ 38 ].…”
Section: Introductionmentioning
confidence: 99%